Social media in an English village : or how to keep people at just the right distance - Miller, Daniel, 1954- (Why we post., 2016)
Daniel Miller spent 18 months undertaking an ethnographic study with the residents of an English village, tracking their use of the different social media platforms. Following his study, he argues that a focus on platforms such as Facebook, Twitter and Instagram does little to explain what we post on social media. Instead, the key to understanding how people in an English village use social media is to appreciate just how 'English' their usage has become. He introduces the 'Goldilocks Strategy': how villagers use social media to calibrate precise levels of interaction ensuring that each relationship is neither too cold nor too hot, but 'just right'. He explores the consequences of social media for groups ranging from schoolchildren through to the patients of a hospice, and he compares these connections to more traditional forms of association such as the church and the neighbourhood. Above all, Miller finds an extraordinary clash between new social media that bridges the private and the public domains, and an English sensibility that is all about keeping these two domains separate.